STUDY OF SUPERCAPACITIVE BEHAVIORS OF Co AND Fe DOPED MANGANESE OXIDES PREPARED BY ANODIC ELECTRODEPOSITION - Thu Hang, Le Thi; Tung, Ngo Duc; Lan Anh, Nguyen Thi; Tung, Mai Thanh (Vietnam Journal of Chemistry, 2012)
Supercapacitive behavior of Co and Fe doped manganese oxide films prepared by anodic deposition were characterized using cyclic voltammetry (CV) and impedance spectroscopy (EIS). Results showed that the highest specific capacitance of 186.2 F/g and stability of 84% obtained with Co doped manganese oxide after scaning 500 cycles. For Fe doped manganese oxide, those parameters were 298.4 F/g and 83%, respectively. The Co, Fe doped manganese oxide film-coated electrodes showed ideal pseudocapacitive behaviors. The appearance of Co and Fe decreased diffuse resistance and charge transfer resistance of the film. They also increased electric double layer capacitance and capacitor response frequency. Keywords: Binary oxide, supercapacitor, manganese dioxide.